Integrating Problem-Based Learning Through Worksheet Development To Enhance Students' Critical Thinking Skills - Fatmawati, Baiq; Khotimah, Husnul; Roshayanti, Fenny; Ha, Minshu (Jurnal Pendidikan Sains Indonesia, 2024)
The principle of problem based learning is to carry out investigations to find the truth by studying theories, asking experts, and also by conducting experiments depending on the problems found. Worksheet based on problem design emphasizes student activities to search for information through various sources such as environmental investigations, studies related to issues according to the content, formulating problems, comparing investigation results, proposing and considering the solutions obtained. The average value results for advisability of the product from the two validators are presentation of content 95%, discussion 85.6% and language 97.5% are very advisability category. Student responses to teaching modules was 100% of students students stated they were eligible. To find out of effect of worksheet based on problem, from the results of statistical tests using the paired sample t test using the SPSS 26 application, it can be concluded that there is a difference in the average student scores before and after implementing the worksheet based on problem. The students' critical thinking test results obtained a gain score of 49.4 with a high category of 58.8%; 41.2% low; and 0% low. The conclusion from this development research is that there is an influence of worksheet based on problem on motion systems content in learning and increasing students' critical thinking. The presence of worksheet based on problem helps the process of training students' higher-level thinking skills